The Embassy in Grosvenor Square - Holmes, Alison R. author. aut Link
XVI, 360 p.
Keywords: Covering the period 1938 to 2008, The Embassy in Grosvenor Square explores the role of the embassy in the Anglo-American 'special relationship', both in terms of transatlantic affairs and issues of international relations.